Effect of Star Board Rewards on Learning Motivation of 4-5 Year-Old Children: A Quantitative Experimental Study: Pengaruh Reward Papan Bintang terhadap Motivasi Belajar Anak Usia 4-5 Tahun: Sebuah Studi Eksperimen Kuantitatif - Alfirdaus, Raudlotul Jannah; Wahyuni , Akhtim (Indonesian Journal of Education Methods Development, 2023)
This study investigates the impact of providing star board rewards on the learning motivation of children aged 4-5 years in Kindergarten Aisyiyah 09 Kranji Lamongan. Using a quantitative experimental approach with a typo one group pretest-posttest research design, the research was conducted in an experimental class comprising 13 students. A motivational questionnaire with 16 questions was used as the assessment instrument, and data collection occurred through pretest and posttest evaluations. The data were analyzed using paired sample t-test, revealing a significant increase in the average value of children's learning motivation by 35.1% from the pretest value to 44.1% in the posttest. Consequently, the findings indicate that giving star board rewards positively influences children's learning motivation (p < 0.05). The implications of this research contribute to our understanding of effective teaching strategies and provide valuable insights for educators and policymakers seeking to enhance children's learning motivation in early education settings. Highlight: The study examines the impact of star board rewards on learning motivation in young children. A quantitative experiment with a typo one group pretest-posttest design was used for data collection. Significant improvement in children's learning motivation was observed after the implementation of star board rewards. Keyword: Star Board Rewards, Learning Motivation, 4-5 Years Old, Kindergarten, Quantitative Experiment